Survey of Interest and Motivation in Playing Basketball in Students of SMK Negeri 1 Indralaya Selatan - Kurniawan, Mhd Idang; Wardiah, Dessy; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
The problems experienced by students have not been able to maximize achievement in basketball. This study aims to find out how much interest and motivation in playing basketball among students of SMK Negeri 1 Indralaya Selatan in participating in extracurricular basketball activities. This research is a quantitative descriptive study using a survey method. The population in this study were class X students who took part in basketball extracurricular activities at SMK Negeri 1 Indralaya Selatan. The instrument in this study used an attitude scale questionnaire/questionnaire, while the sampling technique was purposive sampling. This research was a study involving 32 students in class X who took part in basketball extracurricular activities. All the required data were obtained using observation, documentation and interview techniques with the help of a set of instruments in the form of a questionnaire which had previously been tried out and declared valid and reliable. The data analysis used in this study is a quantitative descriptive analysis with percentages. The conclusion in this study is that interest in playing basketball at State Vocational School 1 Indralaya Selatan for class X participating in extracurricular basketball is in the medium category with a percentage of 41% for 13 students. The motivation for playing basketball at SMK Negeri 1 Indralaya Selatan for class X who took part in extracurricular basketball was in the high category with a percentage of 38% for 12 students.